Integrating Geospatial Intelligence and Digital Transformation for Advancing Environmental Sustainability in Emerging EU Economies - Nicoleta Mihaela Doran; Gabriela Badareu; Marian Ilie Siminică (Applied Sciences)
This study explores the interplay between digital transformation and environmental sustainability in four emerging European Union economies—Bulgaria, Hungary, Poland, and Romania—through the lens of geographic information science and technology (GIS&T). Leveraging panel data from 2010 to 2022, digitalization is quantified through infrastructure, affordability, and user adoption metrics, consolidated into a comprehensive digitalization index. Environmental sustainability is assessed via greenhouse gas emissions and the share of renewable energy in total energy consumption, capturing critical spatial and ecological dynamics. Applying a generalized linear model, the results reveal that enhanced digital infrastructure and affordability contribute to emissions reduction, whereas increased user adoption correlates with higher energy demand and emissions. Furthermore, digitalization fosters improved integration of renewable energy sources, highlighting the strategic role of GIS&T in monitoring and optimizing sustainability initiatives. These insights emphasize the necessity of embedding geospatial analytics into policy frameworks to align digital transformation with environmental and socioeconomic sustainability goals.